PENGARUH KOMITE AUDIT, FINANCIAL TARGET, DAN FINANCIAL STABILITY TERHADAP FINANCIAL STATEMENT FRAUD - Febri, Alvira; Asih Handayani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to analyze and provide empirical evidence of the influence of audit committees, financial targets, and financial ꞩtability on financial statement fraud in financial sector companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. The type of research used in this research is quantitative research using secondary data obtained directly from the official website of the Indonesian Stock Exchange, namely www.idx.co.id. The population in this research is 104 financial sector companies registered on the IDX from 2019 to 2023. The sample used in this research used a purposive sampling technique and the remaining 60 companies met the sampling criteria. The research method used is the multiple linear regression analysis method using the analysis tool, namely Eviews 12. The research results show that the audit committee, financial targets and financial ꞩtability simultaneously influence financial statement fraud. Partially, only financial targets have an influence on financial statement fraud. Meanwhile, the audit committee and financial ꞩtability have no effect on financial statement fraud.